The Protection of the Right to Health Under Article 2 of the European Convention on Human Rights - Milenkovska, Marija (Richtmann Publishing, 2012)
In the case LCB v United Kingdom the European Court of Human Rights (Court) noted that: â€œthe first sentence ofArticle 2 (of European Convention on Human Rights) enjoins the State not only to refrain from the intentional and unlawful takingof life, but also to take appropriate steps to safeguard the lives of those within its jurisdiction.â€ In the case Cyprus v Turkey theCourt observed that:â€œan issue may arise under Article 2 of the Convention where it is shown that the authorities of a ContractingState put an individualâ€™s life at risk through the denial of health care which they have undertaken to make available to thepopulation generally.â€It follows that the obligation to protect life has been extended in the sphere of health care by the Court. Inthis regard, the paper attempts to determine the existence, scope and breach of the positive obligation regarding provision ofhealth care under Article 2 of the ECHR based on the jurisprudence (case-law) of the Court.